What are the Building Blocks of Customer Brand Loyalty in Department Stores? A Multi-Level Mediation Analysis. Issue 4 (2nd October 2017) - Nikhashemi, S. R.; Valaei, Naser
ABSTRACT: Building customer brand loyalty through branding strategies to sustain competitiveness in the retail industry has gathered momentum among researchers. The purpose of this study is to examine the role of brand personality and consumer brand identification on customer brand loyalty via the mediating variables of perceived service quality, perceived value, brand trust, brand commitment, and word-of-mouth communication among Malaysian department stores' customers. Using a self-structured questionnaire, 381 usable responses are considered for data analysis by applying a covariance-based structural equation modeling approach. The results of exploratory factor analysis show that sincerity, followed by sophistication and competence, are the most significant dimensions used to predict brand personality in department stores. The outcomes also reveal that brand personality indirectly influences customer brand loyalty via consumer brand identification. Furthermore, perceived service quality, perceived value, brand trust, word-of-mouth communication, and brand commitment mediate the effects of consumer brand identification on brand loyalty. Finally, the proposed competing model implies that the indirect impact of brand personality and consumer brand identification is inevitable in building department stores' brand loyalty.